Solar Neutrino Physics Oscillations: Sensitivity to the Electronic Density in the Sun's Core - Lopes, Ilidio (2014)
Solar neutrinos coming from different nuclear reactions are now detected with high statistics. Consequently, an accurate spectroscopic analysis of the neutrino fluxes arriving on Earth's detectors becomes available, in the context of neutrino oscillations. In this work, we explore the possibility of using this information to infer the radial profile of the electronic density in the solar core. So, we discuss the constraints on the Sun's density and chemical composition that can be determined from solar neutrino observations. This approach constitutes an independent and alternative diagnostic to the helioseismic investigations already done. The direct inversion method, which we propose to obtain the radial solar electronic density profile, is almost independent of the solar model.